Implementation of Material Process Standard Operational Procedures - Akib, Haedar; Rismawati, Fitrya Lia; Niswaty, Risma (Universitas Negeri Makassar, 2023)
Standard Operational Procedures are work guidelines that are very important for a company to implement properly because they function as a legal basis and guidelines to minimize errors in work implementation. This research aims to find out how standard operational procedures for material processing are implemented in the logistics sub-sector of PT PLN (Perseor) UP3 South Makassar. Data collection techniques through observation, interviews, and documentation. The research results show that the implementation of standard operational procedures has been implemented well, this can be seen from each dimension, namely the work efficiency dimension which has been efficient, the employee work consistency dimension has been consistent but there is still a flow of activities that are not being implemented. Dimension Minimization of errors that employees can make in work activities. Dimensions Problem resolution can be done by employees carrying out existing procedures. The work protection dimension has been implemented well. Appropriate work map dimensions. This research presents new information regarding the implementation of standard operational procedures for material processes in more detail by linking the theory and locus in this research which is different from previous research, namely in the logistics sub-sector of PT PLN (Persero) UP3 South Makassar. So this research can be used as evaluation material for research loci to improve employee work consistency through the implementation of good standard operational procedures